1961
DOI: 10.1084/jem.114.5.791
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of a Rheumatoid Factor-Like Substance in Rabbits

Abstract: Serum factors possessing some of the properties of the human rheumatoid factor(s) (RF) 1 have been produced in experimental animals. The RF and the experimentally induced factors react with various gamma globulins. The anti-gamma globulin specificities of experimentally induced serum factors can be attributed to one or more of the following mechanisms:(a) The production of antibodies against heterologous gamma globulin as in Adler's study (1) where sensitized sheep cell agglutinins developed in the serum of gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1
1

Year Published

1962
1962
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(56 citation statements)
references
References 23 publications
3
51
1
1
Order By: Relevance
“…The two pools of anti-IgE antiserum used for the gel filtration experiments described above were tested. The signals (cpm) thus obtained per 1 (24,25). It should also be of considerable interest to attempt to generate high titers of anti-IgD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two pools of anti-IgE antiserum used for the gel filtration experiments described above were tested. The signals (cpm) thus obtained per 1 (24,25). It should also be of considerable interest to attempt to generate high titers of anti-IgD.…”
Section: Methodsmentioning
confidence: 99%
“…The appearance of anti-globulin autoantibodies, most frequently IgM anti-IgG, is observed after immunization with certain bacteria (1,2), heterologous proteins (3,4), or immune complexes (5,6). It has been suggested that polymers of IgG, such as occur in immune complexes, may cause the IgG to act as a thymus-independent antigen (3).…”
mentioning
confidence: 99%
“…This concept is supported by the findings of Milgrom and Dubiski (22) of rheumatoid factor-like substances in rabbits immunized with isologous antigen-antibody complexes. Rheumatoid factor-like substances have also been demonstrated in rabbits immunized with pure ovalbumin (23) and with E. coli grown on a synthetic medium (24). The immune complexes (ovalbumin-antiovalbumin, E. coli-anti-E. coli) produced in these animals presumably stimulated the production of rheumatoid-like factors.…”
Section: Resultsmentioning
confidence: 99%
“…With the sera from animals after a second injection of BGG such inactivation by mercaptoethanol treatment was not observed, indicating that most of the antibody produced was 7S rather than 19S gamma globulin (10).…”
Section: Serum Antibody Titers During the Secondary Response To Bgg-mentioning
confidence: 93%